Making room : recovering hospitality as a Christian tradition - Pohl, Christine D (Grand Rapids, MI William B Eerdmans Publishing Company, 1999)
For most of church history, hospitality was central to Christian identity. Yet our generation knows little about this rich, life-giving practice. In Making Room, Christine Pohl revisits the discipline of welcoming strangers and provides the foundation for renewed commitment to recovering hospitality as a Christian tradition. Combining biblical and historical research with extensive interviewing of people in contemporary communities of hospitality--the Catholic Worker, L'Abri, L'Arche, Good Works, Jubilee Partners, St. John's Abbey, and others--Pohl explores the necessity, difficulty, and blessing of practicing hospitality today
For most of church history, hospitality was central to Christian identity. Yet our generation knows little about this rich, life-giving practice. In Making Room, Christine Pohl revisits the discipline of welcoming strangers and provides the foundation for renewed commitment to recovering hospitality as a Christian tradition. Combining biblical and historical research with extensive interviewing of people in contemporary communities of hospitality--the Catholic Worker, L'Abri, L'Arche, Good Works, Jubilee Partners, St. John's Abbey, and others--Pohl explores the necessity, difficulty, and blessing of practicing hospitality today
Includes bibliographical references (pages 196-200) and index
Keywords: Hospitality -- Religious aspects -- Christianity; Christian life